The Effect of Sustainability Report Disclosure, Environmental Costs and ISO 14001 Certification on Company Value in Mining Sector Companies Listed on the Indonesia Stock Exchange - Tampubolon, Michael Yitro; Putri Wahyuni (Sekolah Tinggi Ilmu Ekonomi Eka Prasetya, 2024)
This study aims to find out whether the disclosure of Sustainability Report, Environmental Costs and ISO 14001 Certification has a significant effect on the Company Value of mining sector companies listed on the Indonesia Stock Exchange. This study uses quantitative data types and the data source is secondary data. The population in this study is all mining sector companies listed on the Indonesia Stock Exchange starting from the 2019-2023 period which totals 71 companies. The sample from this study amounted to 14 companies for 5 years, namely the 2019-2023 period, namely 70 samples, which were obtained by purposive sampling technique. Data analysis and testing consisted of descriptive statistics, classical assumption tests, multiple regression analysis, partial hypothesis testing (T test) and simultaneously (F test), and determination coefficient test. The results of this study show that the Disclosure of the Sustainability Report has no effect and is not significant on the Company's Value with a calculated T value of 0.035 < T Table 2.01063 with a sig value of 0.972 > 0.05. Environmental Costs have a significant effect on the Company's Value with a calculated T value of 2.477 > T table 2.01063 with a sig value of 0.017 < 0.05. ISO 14001 certification has a significant effect on the Company's Value with an mT value calculated at 3.446 > T table 2.01063 with a sig value of 0.001 < 0.05. The disclosure of Sustainability Report, Environmental Costs, ISO 14001 Certification simultaneously had a significant effect on the Company's Value with an F value of 6.618 > an F value of 2.80 table with a sig value of 0.001 < 0.05. The value of the regression coefficient was 25.2%.